Prospecção in vitro de associações antifúngicas sinérgicas para Fusarium spp - Venturini, Tarcieli Pozzebon (2010)
The genus Fusarium is characterized by hyaline filamentous fungi that cause a wide spectrum of infections predominantly in immunocompromised patients. These fungal infections show high rates of morbidity and mortality and are difficult to diagnosis, to prevent and to treat. The remarkable primary resistance to antifungal agents of this genus requires the search for new therapeutic possibilities. An attempt is a combination of drugs with different mechanisms of action. This study aimed to evaluate the in vitro susceptibility of Fusarium to conventional antifungal agents (amphotericin B, itraconazole, and voriconazole) and their combinations with no antifungal drugs (azithromycin, ciprofloxacin, fluvastatin, ibuprofen, metronidazole, and rifampicin) against 27 isolates of Fusarium spp. including the species: F. chlamydosporum (3), F. nygamai (1), F. oxysporum (6), F. proliferatum (2), F. solani (11), F. sporotrichoides (1), and F. verticillioides (3). Based on the protocol M38-A2 (CLSI, 2008) the technique of checkerboard was used for the assessment of associations. Alone, the MICs for amphotericin B ranged from 0.125 - 4 μg/ml; for voriconazole they ranged from 1 - >16 μg/ml, and for itraconazole all isolates showed MICs > 16 μg/ml. All combinations with amphotericin B showed synergistic interactions, and the most effective were amphotericin B plus ibuprofen (44.4%), amphotericin B plus metronidazole (40.7%), and amphotericin B plus ciprofloxacin (37%). No antagonistic interactions were observed for associations with amphotericin B. Similarly, all associations with voriconazole showed synergism, and the most significant associations were voriconazole plus ciprofloxacin (33.3%) and voriconazole plus metronidazole (33.3%). The antagonism was observed in all associations with voriconazole against F. verticillioides. The associations with itraconazole showed indifferent interactions for 100% of the isolates tested. These results demonstrate that the in vitro antifungal activity of the drug combination showed better results than the isolated one, except for associations with itraconazole. The most significant associations with amphotericin B and voriconazole deserve in vivo evaluations in order to verify their potential in the treatment of fusariosis.